KARAKTERISTIK EDIBLE FILM DARI TAPIOKA DENGAN PENAMBAHAN GELATIN - ., Rosalyn; Utomo, Adrianus Rulianto; Setijawati, Erni (Jurnal Teknologi Pangan dan Gizi, 2016)
Packaging on the market is generally made of plastic. Plastic polymers have several weaknesses, such as, causing contamination through transmission of monomers from the plastic to the packed material and especially the disability of the packaging to be degraded by nature (non-biodegradable) that can cause pollution to the environment. One of the alternatives to overcome this problem is to make both easy to degrade by nature and safe to be eaten packaging. The raw material for making edible film is tapioca. Tapioca has economic advantages, a renewable resource, and is able to provide the flexibility and transparency of the edible film. However, edible film made of tapioca alone still has a few weaknesses, which are easy to tear and less strength to withstand loads that can be overcame with the use of gelatin. This research uses data analysis in the form of a mathematical model consisting of one (1) factor, namely the addition of gelatin concentration. Each treatment is repeated three (3) times, so there are 21 experimental units. The parameters to be tested are water content, Water Activity (Aw), tensile strength, and percent elongation. The data obtained from each test will be analyzed by finding a mathematical model using regression analysis. The water content of edible film ranges from 12.34% - 12.75%. aw edible film ranges from 0.529 to 0.573. Edible film tensile strength ranging from 46.6 kg / cm 2 - 374,21kg / cm 2. Percent elongation of edible film ranges between 4% - 13%.